Human Immunodeficiency Virus Type 1 and Related Primate Lentiviruses Engage Clathrin through Gag-Pol or Gag - Popov, Sergei (American Society for Microbiology, 2011)

(untitled)
The Gag-Pol polyprotein of human immunodeficiency virus type 1 (HIV-1) is not required for efficient viral particle production. However, premature termination codons in pol, particularly in the integrase (IN)-coding region, can markedly impair HIV-1 particle formation, apparently due to the premature activation of the viral protease (PR). We now report that the IN domain of Gag-Pol is required for the incorporation of clathrin into HIV-1 virions. Significantly, PR-dependent effects of point mutations in IN on particle production correlated strictly with their effects on clathrin incorporation. A possible interpretation of these findings is that certain IN mutations impair particle production in a PR-dependent manner by promoting Gag-Pol dimerization, which also occludes a binding site for clathrin. Consistently with this model, the reverse transcriptase (RT) inhibitor efavirenz, which is thought to promote Gag-Pol dimerization, inhibited the incorporation of clathrin into HIV-1 virions. Clathrin-depleted cells produced normal amounts of HIV-1 virions; however, their infectivity was reduced. We also observed that HIV-2 and the simian immunodeficiency virus SIVmac interact with clathrin through one or two copies of a peptide motif in the p6 domain of Gag that resembles the clathrin box of cellular adaptor proteins. Furthermore, the substitution of the hydrophobic residues in the single clathrin box motif of SIVmac caused a replication defect in primary cells. Taken together, our results indicate that primate lentiviruses from two different subgroups functionally interact with clathrin during assembly.